Upregulation of TXNIP contributes to granulosa cell dysfunction in polycystic ovary syndrome via activation of the NLRP3 inflammasome. (5th February 2023) - Wang, Ying; Yang, Jiyu; Wang, Yu; Chen, Yao; Wang, Yiran; Kuang, Hongying; Feng, Xiaoling
Abstract: Polycystic ovary syndrome (PCOS) is a complex endocrine disease. Thioredoxin-interacting protein (TXNIP) promotes oxidative stress and triggers inflammation. Herein, we investigated the role and potential mechanism of TXNIP in PCOS. In a mouse model of dehydroepiandrosterone (DHEA)-induced PCOS, we found that TXNIP was upregulated in the ovaries, especially in granulosa cells (GCs). TXNIP was also upregulated in testosterone (T)-treated GCs in vitro. Knockdown of TXNIP by lentivirus-constructed shRNA attenuated T-induced GC injury and oxidative stress, as well as inflammation and the NLRP3 inflammasome. The mechanism by which TXNIP promotes inflammation may involve TXNIP dissociation from the TXNIP-TRX complex and binding to NLRP3 to form the inflammasome. Additionally, we verified that knockdown of TXNIP ameliorated ovarian injury and inflammation in mice with DHEA-induced PCOS in vivo. Collectively, we demonstrated that TXNIP is involved in GC inflammation by promoting NLRP3 inflammasome activation in PCOS. Highlights: TXNIP is up-regulated in the ovary of DHEA-induced PCOS mice. TXNIP is up-regulated in the testosterone-treated granulosa cells. TXNIP contributes to the testosterone-induced granulosa cell injury. TXNIP dissociates from TXNIP-TRX complex and binds to NLRP3 to activate inflammasome. TXNIP contributes to the DHEA-induced PCOS in mice.